PENGARUH EVENT SERVICE QUALITY, EVENT COST DAN EVENT CONVIENIENCE TERHADAP EVENT VENUE SATISFACTION DI JAKARTA CONVENTION CENTRE - Arif Zulkarnain (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
The purpose of this research was to show how value equity and its subdimentiosnof service quality, cost, and convenience drive customer satisfaction among visitors whoare attending events attending events at Jakarta Convention Centre.The design of this research applies a survey to interview the customers for testingthe hypothesis. Meanwhile the required data consist of four variables are event servicequality, event cost and event convenience as dependent variable and event venuesatisfaction as independent variable. The aggregate numbers of customer being respondentof the study are 117 customer.Data analysis used in this research was consists of Structural Equation Modellingby AMOS 6.0 as software. The result of this research concludes that perceived service fromthe visitor of Jakarta Convention Centre should be considered by the management becausein fact most of respondents show the low level of satisfaction from point service quality tounderstand the expected service to achieve event satisfaction.Keywords : event service quality, event cost, event convenience and event venue satisfaction